Salmeterol and physical performance at -15 degrees C in highly trained nonasthmatic cross-country skiers - Sue-Chu, M.; Sandsund, M.; Helgerud, J.; Reinertsen, R. E.; Bjermer, L. (Scandinavian Journal of Medicine & Science in Sports, 1999)
The aim of this double-blind, placebo-controlled, cross-over study was to investigate possible improvement in physical performance at an ambient temperature of -15 degrees C by an inhaled dose of 50 micrograms salmeterol in 8 highly trained nonasthmatic cross-country skiers. FEV1 was measured before, during and after the treadmill exercise protocol, which consisted of a warm-up run, runs of 10 min at 90% and 5 min at 80% VO2max, followed by a timed run to exhaustion. Despite a significant improvement in FEV1, salmeterol did not have a beneficial effect on heart rate, blood lactate concentration, respiratory exchange ratio, oxygen uptake or minute ventilation during the exercise protocol. Running time to exhaustion was not significantly different from placebo. This lack of enhancement of exercise performance in healthy endurance athletes further supports the recent approval of salmeterol for prophylactic use by asthmatic athletes during training and competition. Scand J Med Sci Sports 1999 Feb;9(1):48-52